2014
DOI: 10.1038/ajg.2014.323
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Location of Diverticular Disease and the Irritable Bowel Syndrome: A Multicenter Study in Japan

Abstract: OBJECTIVES:No previous reports have shown an association between location of diverticular disease (DD) and the irritable bowel syndrome (IBS).METHODS:We included 1,009 consecutive patients undergoing total colonoscopy in seven centers in Japan from June 2013 to September 2013. IBS was diagnosed using Rome III criteria, and diverticulosis was diagnosed by colonoscopy with transparent soft-short-hood. Left-sided colon was defined as sigmoid colon, descending colon, and rectum. Right-sided colon was defined as ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 26 publications
1
33
2
4
Order By: Relevance
“…Among patients with CD, about 10% had inflammatory findings. Some reports (including ours) showed a relationship between CD and diarrhea . Initially, we supposed that patients with inflammatory findings had diarrhea; however, this study showed no such association.…”
Section: Discussioncontrasting
confidence: 72%
“…Among patients with CD, about 10% had inflammatory findings. Some reports (including ours) showed a relationship between CD and diarrhea . Initially, we supposed that patients with inflammatory findings had diarrhea; however, this study showed no such association.…”
Section: Discussioncontrasting
confidence: 72%
“…La incidencia de la diverticulosis aumenta desde < 16% en pacientes menores de 40 años a > 63% en mayores de 70 años 4 . Su ubicación más frecuente es a nivel de sigmoides, sin embargo, en países de Asia se localizan principalmente en colon ascendente 5 . La historia natural de la diverticulosis no está aclarada.…”
Section: Epidemiologíaunclassified
“…Recent evidence that diverticulosis is associated with IBS [12,13] and patients with diverticulitis can lack fever and leukocytosis [3,4,8,9,14] could contribute to misdiagnosis.…”
Section: Introductionmentioning
confidence: 98%